Multifaceted [36]octaphyrin(1.1.1.1.1.1.1.1): deprotonation-induced switching among nonaromatic, Möbius aromatic, and Hückel antiaromatic species. Issue 36 (12th April 2016) - Cha, Won-Young; Soya, Takanori; Tanaka, Takayuki; Mori, Hirotaka; Hong, Yongseok; Lee, Sangsu; Park, Kyu Hyung; Osuka, Atsuhiro; Kim, Dongho
Abstract : Deprotonation of a nonaromatic octaphyrin with TBAF affords a monoanionic twisted Möbius aromatic species or a dianionic square Hückel antiaromatic species, depending upon the amount of TBAF. Abstract : Deprotonation of nonaromatic octakis-(pentafluorophenyl)-substituted [36]octaphyrin(1.1.1.1.1.1.1.1) with tetrabutylammonium fluoride (TBAF) afforded monoanionic twisted Möbius aromatic species and dianinonic square Hückel antiaromatic species, depending upon the amount of TBAF.